Musical Analysis of The Song Homesickness - Zhang, Jiayue (Transactions on Social Science, Education and Humanities Research, 2025)
In 1979, with the broadcast of the televised scenic documentary The Legend of the Three Gorges, the featured song Homesickness emerged as a representative work of the period. Its innovative artistic expression sparked widespread discussion. While existing research has largely focused on the cultural implications of the piece, systematic analyses of its musical structure remain rare. This paper explores Homesickness from three dimensions—musical form, vocal techniques, and cultural connotations—to examine how it integrates contemporary elements into traditional compositional frameworks. The aim is to provide insights for future scholarly inquiry and creative practice. The study reveals that the song employs a parallel tripartite structure, fusing Western functional modal harmony with narrative melodies rooted in Chinese folk traditions. Rhythmic displacement, accent shifts, and modern instrumentation such as the electric guitar disrupt conventional rhythmic patterns, enhancing dramatic expression. The vocalist, Li Guyi, pioneered the “semi-voiced singing technique,” blending ornamental elements from Hunan flower-drum opera with bel canto breath control, thereby achieving a personalized mode of emotional delivery. The cultural significance of Homesickness lies not only in its pioneering role as the first popular song after China’s Reform and Opening-Up but also in its innovative combination of musical form and ideological transformation. It serves as both a technical model and an aesthetic reference for the development of contemporary Chinese popular music.